First Year University Students' Use of Formulaic Sequences in Oral and Written Descriptions - Eric Gómez Burgos (Universidad Nacional de Colombia, 2015)
The present article investigates the use of first year university students' formulaic sequences in written and oral texts in an English as a foreign language context. The corpus of the study consists of eight descriptive texts-four written and four oral-which were composed of four students of English Pedagogy at a university in Santiago, Chile. The investigation is a case study where the corpora were analysed qualitatively. The results show that first-year students use similar formulaic sequences in written and oral texts and many of the expressions generally used in spoken discourse are used by students in written texts.